Changes in the similarity of business structure and demography after European Union accession - Kamińska, Teresa; Zielenkiewicz, Małgorzata (Zmiany w upodabnianiu się krajów pod względem struktury i demografii biznesu po akcesji do Unii Europejskiej, 2019)
The article is intended to be a ‘balance sheet’ of integration process in the framework of the European Union as regards the biggest enlargement after 2004. The subject of the studies are the 23 economies of the EU and Norway over the period 2006-2016 in the aspect of whether the new entrants followed more advanced countries. The concept of economic convergence has been assumed as the most crucial theoretical notion explaining the process of assimilation between members of the EU. A cognitive aim is to test whether the integration has induced convergence of the EU countries in terms of ‘structure and demography of business’. The hypothesis states that the new entrants to the EU have neared the old members, however they still retain their specificity related to the post-socialistic system. In order to reach the goal and solve tasks, a comparative analysis, a statistical analysis, Euclidean distance and cluster analysis were applied for revealing the dynamics of the process of making economies more similar
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 6, s. 51-63
Keywords: integration; European Union; convergence; business structure; business demography; integracja; Unia Europejska; konwergencja; struktura biznesu; demografia biznesu